Dahlia variabilis cultivar 'Seattle' as a model plant for anthochlor biosynthesis - Walliser, Benjamin (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2020 The Author(s). Published by Elsevier Masson SAS.. All rights reserved.